Febrile Illness Outbreak Investigation in Sundarharicha-5 Foklan Tapu, Morang District - Pandey, Ashok; Sah, Arun Kumar; Belbase, Pradeep; Sah, Anil Kumar; Jha, Anjani Kumar (Journal of Nepal Health Research Council, 2019)
Background: On the date of 24 July 2017, the major national daily newspaper reported that there were two death cases from an unknown disease in the Morang district, Sundarharicha Municipality 5, Foklan Tapu. A team of researcher and experts were mobilized in the affected area to investigate and identify the etiological and epidemiological causes. Methods: Both qualitative and quantitative methods was used to conduct the outbreak investigation. 83 blood samples were taken from the patients and microbiological analysis was done at National Public Health Laboratory, Kathmandu. Similarly, 2 verbal autopsies and 5 Key in-depth interviews were taken from a local community leader, local health service providers, medical officer of Koshi Zonal Hospital, district public health officer and medical director of WHO. Results: Out of 83 participants, 49% and 25% of the participants were positive to IgM and IgG antibodies of Leptospira species respectively. 87% of the participants were exposed to animal living in his/her home (including pets). Conclusions: An outbreak which was existing during this investigation turned out to be leptospirosis outbreak, whose exposure was consumption of unhealthy meat during social gathering. Keywords: Epidemiological; etiological; febrile illness; outbreak investigation.